Combat stress in conflicts: Home and abroad - Pattanaik, Atanu K. (Journal of Defence Studies)
International peacekeeping operations have been one of the hallmark developments in the post-Cold War era. While it is true that these operations started almost immediately after the end of World War II, they really gathered momentum post the fall of Berlin Wall in 1989. The shadow of veto by warring permanent members gave way to cooperation and greater consensus emerged to solve the world$1 (Bs problems in trouble spots through United Nations (UN)-led multinational peacekeeping operations. The UN peacekeeping has a long but checkered history. With around 70,000 soldiers deployed in faraway trouble spots, the UN peacekeeping operations provide a fertile ground to study a vital area of health and well-being, namely combat stress.1- Reproduced s